Evaluation of organic acidifiers as a corrective measure for high bicarbonate concentrations in organic tobacco (Nicotiana tabacum L.) float bed systems. (25th February 2021) - Suchoff, David H.; Short, Maggie M.; Vann, Matthew C.; Stevens, Drake A.; McGinnis, Michelle S.; Crump, Kenneth K.
Abstract: Interest in the production of USDA-certified organic tobacco continues to increase. Limited research exists that focuses on organic production practices specific to tobacco. Float beds, a semi-hydroponic system, are commonly used to germinate seed and produce healthy transplants. High bicarbonate concentrations in the float bed solution are a common issue and can greatly affect seedling health. A greenhouse experiment was conducted to evaluate OMRI-certified acidifier treatments for their effects on float bed media and solution nutrient status and plant health. Treatments included acetic acid, liquid citric acid, granular citric acid, a sulfuric acid conventional check, and stagnant and aerated controls. Miniature float beds were constructed to which the acidifier treatments were applied, each containing a single 288-cell tray and fertilized with seabird guano. The aerator treatment was the only one to consistently maintain bicarbonate levels below the recommended 100 mg L −1 . Aeration also created an environment that favored high nitrate and low ammonium concentrations compared to all other treatments. Dissolved oxygen remained at or above 6 mg L −1 with aeration, while the remaining five treatments resulted in concentrations below 4 mg L −1 . No significant differences were found among the acidifier treatments for percent of usable transplants produced. Media selection may play a role in buffering the extreme bicarbonate concentrations, as the pH in the media tended to be lower than the more alkaline solution. The use of an aerator proved to be an effective means to manage high bicarbonate and appears to promote higher rates of nitrification of the organic fertilizer source material.